2016
DOI: 10.3847/0004-637x/826/1/10
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Coronal Mass Ejections

Abstract: We analyze the physical origin of plasmas that are ejected from the solar corona. To address this issue, we perform a comprehensive analysis of the elemental composition of interplanetary coronal mass ejections (ICMEs) using recently released elemental composition data for Fe, Mg, Si, S, C, N, Ne, and He as compared to O and H. We find that ICMEs exhibit a systematic abundance increase of elements with first ionization potential (FIP) < 10 eV, as well as a significant increase of Ne as compared to quasi-statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 53 publications
4
46
0
Order By: Relevance
“…It is possible, and indeed likely, that an important systematics is still at play, namely that we cannot completely exclude a small amount of residual fractionation in these regions. However, it has been shown that any unaccounted residual fractionation would go in the direction of reducing the measured metallicity, and thus, the derived metallicity Z is actually a lower limit to the photospheric metallicity [17,[21][22][23][24][25]. In view of the recent downward revisions that have led to the "solar modeling problem", such a measurement can provide a very important cross-check to the values of metallicity obtained through spectroscopy.…”
Section: In Situ Solar Wind Measurements Of Metallicitymentioning
confidence: 97%
“…It is possible, and indeed likely, that an important systematics is still at play, namely that we cannot completely exclude a small amount of residual fractionation in these regions. However, it has been shown that any unaccounted residual fractionation would go in the direction of reducing the measured metallicity, and thus, the derived metallicity Z is actually a lower limit to the photospheric metallicity [17,[21][22][23][24][25]. In view of the recent downward revisions that have led to the "solar modeling problem", such a measurement can provide a very important cross-check to the values of metallicity obtained through spectroscopy.…”
Section: In Situ Solar Wind Measurements Of Metallicitymentioning
confidence: 97%
“…Among all solar wind samples in the heliosphere, solar wind from polar coronal holes (PCHs) is the least fractionated of all samples of steady state of transient solar wind flows (Zurbuchen 2007;Zurbuchen et al 2012;Zurbuchen et al 2016). Even in PCH-associated wind, there is still some fractionation, especially of insufficient collisional coupling that affects all of solar wind, but is most evident in He/H (Geiss et al 1970).…”
Section: In Situ Solar Wind Measurements Of Metallicitymentioning
confidence: 99%
“…On the other hand, the elemental ratios depend, in a complex way, on chromospheric temperatures, the magnetic field configuration at the origin of the plasma, and the plasma confinement time before the release (e.g., Laming (2015), and references therein). In ICMEs, increased amounts of high charge states of elements such as Fe, Ne, Si, Mg are often observed suggesting extended confinement times (e.g., Lepri et al 2001;Zurbuchen et al 2016).…”
Section: General Icme Signaturesmentioning
confidence: 99%